NAFTA and Wage Inequality in Mexico: An Analysis for Border Cities, 1992-2016 - AGUILERA FERNÁNDEZ, Albany; CASTRO LUGO, David (Frontera Norte, 2018)
The purpose of this article is to evaluate the impact of the NAFTA on the labor market and wage inequality in border cities in the north of Mexico, emphasizing the variations among workers according to their qualifications and gender from 1992 to 2016. Using data from the National Survey of Urban Employment and the National Survey of Jobs and Employment, the microsimulation methodology was applied. The results suggest that if the labor structure that existed before the consolidation of the commercial opening under NAFTA had stayed in place, the levels of wage inequality would have been lower than those observed in 2016.